1980
DOI: 10.1021/bi00553a019
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent effects of sodium butyrate in Chinese hamster cells: cell-cycle progression, inner-histone acetylation, histone H1 dephosphorylation, and induction of an H1-like protein

Abstract: This paper presents the first unified quantitative study of the effects of butyrate concentration upon (1) cell-cycle progression, (2) modification of all inner histones, (3) dephosphorylation of histone H1, and (4) enhancement of an H1-like protein (BEP) in CHO cells. Flow cytometric analysis shows that exposure to butyrate enriches CHO cultures in G1 cells and, at sufficient butyrate concentration, leads to G1 arrest. Additionally, butyrate alters the rate of cell-cycle progression through G2/M and through S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
84
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(94 citation statements)
references
References 79 publications
10
84
0
Order By: Relevance
“…This inhibition did not occur when expression of another nuclear proto-oncogene, c-myb, (30). Conversely, H1" accumulates in cultured cells when growth has been arrested (9,37,39) and in adult tissues containing a high proportion of nondividing cells (36). It also is present in the chromatin of certain terminally differentiated cells, including MEL cells (12,22,35).…”
Section: Resultsmentioning
confidence: 99%
“…This inhibition did not occur when expression of another nuclear proto-oncogene, c-myb, (30). Conversely, H1" accumulates in cultured cells when growth has been arrested (9,37,39) and in adult tissues containing a high proportion of nondividing cells (36). It also is present in the chromatin of certain terminally differentiated cells, including MEL cells (12,22,35).…”
Section: Resultsmentioning
confidence: 99%
“…An orally bioavailable transcriptional inducer of ␥-globin that does not have cellular growth-inhibitory properties and could be administered more frequently to stimulate a further increase in the proportion of HbF-containing cells (F cells) would be therapeutically advantageous for ␤-globin disorders. 14 Butyrate (at 1-6 mM) inhibits cellular proliferation and entry into S phase, in a wide variety of cell types, [15][16][17][18][19][20][21][22] consistent with a reversible cell cycle arrest at the G 1 phase of the cell cycle. [23][24][25][26][27] The precise mechanisms of butyrate-induced G 1 arrest have not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It was reported that NaBu induces apoptotic cell death 8 and arrests cells at the G 1 phase of the cell cycle. 9 Biopharmaceutical companies have become a multi billion-dollar industry, generating various recombinant proteins. In industries, it is important to engineer genes that function in cell growth and survival, design serum/protein-free media, and improve the culture process in order to achieve an overall production level cost-effectively.…”
mentioning
confidence: 99%